Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1152/ajpendo.1997.272.4.e567
|View full text |Cite
|
Sign up to set email alerts
|

Brain of the conscious dog is sensitive to physiological changes in circulating insulin

Abstract: The aim of this study was to determine whether a selective, physiologically relevant increase in blood-borne insulin perfusing the brain has an impact on the counterregulatory response to hypoglycemia. Experiments were carried out on 12 conscious 18-h-fasted dogs. Insulin was infused (1 mU x kg(-1) x min(-1)) in separate, randomized studies into a peripheral vein (n = 6) or both carotid and vertebral arteries (n = 6). This resulted in equivalent systemic insulinemia (38 +/- 2 vs. 35 +/- 5 microU/ml) but differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
2
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 9 publications
4
22
2
1
Order By: Relevance
“…However, with long-term intranasal treatment we did not find any hints towards an elevating effect of insulin on blood pressure in humans [35]. These findings fit well with animal studies indicating that long-term in contrast to immediate central nervous insulin administration does not affect arterial blood pressure [34,36,37,38]. On this background, our data point to a gradual activation of counterregulatory mechanisms during prolonged treatment with insulin.…”
Section: Intranasal Administration Of Insulinsupporting
confidence: 86%
See 1 more Smart Citation
“…However, with long-term intranasal treatment we did not find any hints towards an elevating effect of insulin on blood pressure in humans [35]. These findings fit well with animal studies indicating that long-term in contrast to immediate central nervous insulin administration does not affect arterial blood pressure [34,36,37,38]. On this background, our data point to a gradual activation of counterregulatory mechanisms during prolonged treatment with insulin.…”
Section: Intranasal Administration Of Insulinsupporting
confidence: 86%
“…Accordingly, circulating insulin and glucose levels also do not change during prolonged (8 weeks) of intranasal treatment with insulin (160 IU/day) [32, 33]. Since animal experiments have indicated that central nervous insulin can induce acute sympathoexcitation via central nervous autonomous centers [34], the possible therapeutic use of intranasal insulin administration might be hampered by elevating effects on blood pressure. However, with long-term intranasal treatment we did not find any hints towards an elevating effect of insulin on blood pressure in humans [35].…”
Section: Intranasal Administration Of Insulinmentioning
confidence: 99%
“…Finally, neural pathways stimulated by hypoglycemia induce feeding behavior [2]. Hormone responses and symptoms of hypoglycemia tend to be blunted in DM patients treated with insulin, and it is likely that deficient responses to hypoglycemia result from recurrent severe hypoglycemia sustained over many years of insulin replacement [1] CNS mechanisms of autonomic and endocrine responses to hypoglycemia have been studied in dogs and in rodents, and these studies indicate participation of structures in brainstem as well as hypothalamus [3][4][5][6][7][8][9][10][11][12]. Although these animal studies have proven useful in elucidating aspects of neural circuitry underlying counterregulatory hormone secretion, symptom thresholds, per se, cannot be directly assessed in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our experiments argue against a role for vagal afferents in the initiation of the counterregulatory response to insulin-induced hypoglycemia. On the other hand, Davis et al (9,10) demonstrated that during insulin-induced hypoglycemia in conscious dogs, the brain insulin level is a key determinant of the magnitude of the counterregulatory response, such that higher insulin levels markedly augment the sympathetic response to hypoglycemia. The concept that the insulin concentration can modify the counterregulatorry response to hypoglycemia has also been demonstrated in nondiabetic (11,12) and diabetic humans (13,14).…”
mentioning
confidence: 99%